ACCEPTANCE AND IMPACT AARHUS CONVENTION ON ACCESS TO ENVIRONMENTAL INFORMATION IN UKRAINE - Проскура, Ганна Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article reveals the issue of adoption and influence of the Aarhus Convention in the context of the development of access to environmental information. Methods of research: the list of normative legal acts and international agreements in this field is determined. The methodological basis of the research comprise general scientific methods of scientific knowledge, such as integrated and interdisciplinary. Results: the main preconditions and requirements for the adoption and impact of the Aarhus Convention in the context of the development of access to environmental information are determined. Conclusion is made regarding the impact of the Aarhus Convention on access to environmental information in Ukraine. Discussion: problems of national and international legislation and implementation of norms of foreign legislation to the norms of domestic legislation in the field of access to environmental information.